1995
DOI: 10.1021/ja00128a029
|View full text |Cite
|
Sign up to set email alerts
|

Organoactinide-catalyzed oligomerization of terminal acetylenes

Abstract: Various actinide alkyl and hydride metallocenes effectively and selectively catalyze a variety of C-H bond activation and hydrogenation reactions.1 In their "cationic" form, these d°/f°m etallocene complexes have recently been shown to be very

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 0 publications
2
57
0
1
Order By: Relevance
“…The same regioselective insertion of TMSCMCH to an organothorium alkenyl complex was observed in organoactinide-catalyzed oligomerization of alkynes. 88,89 ð20Þ ð21Þ…”
Section: Catalytic Hydrosilylation Of Terminal Alkynes Catalytic Hydr...mentioning
confidence: 99%
“…The same regioselective insertion of TMSCMCH to an organothorium alkenyl complex was observed in organoactinide-catalyzed oligomerization of alkynes. 88,89 ð20Þ ð21Þ…”
Section: Catalytic Hydrosilylation Of Terminal Alkynes Catalytic Hydr...mentioning
confidence: 99%
“…Compared to the hundreds of reported transition metal and lanthanide hydrides, there are only a limited number of thorium and uranium hydride complexes. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] The bis(pentamethylcyclopentadienyl) complexes [(C 5 Me 5 ) 2 An(H)(m-H)] 2 (An = Th (1), U (2)) were the first isolable organoactinide hydride complexes; 12 and since their introduction in 1982, they have displayed a palette of chemical reactivity such as the stoichiometric and catalytic hydrogenation of unsaturated substrates, 9,12,[15][16][17] the catalytic dimerization of propylene, 18,19 coupling reactions, [20][21][22] and multi-electron reductions (following liberation of H 2 ). 13,14,[23][24][25] The chemistry of actinide hydrides is still not well understood.…”
mentioning
confidence: 99%
“…Uranium(IV) complexes have also been documented for the oligomerization of alkynes, as early as 1995, when [(Cp*) 2 U(Me) 2 ] ( 5 ) was found to catalyze the synthesis of alkyne trimers and dimers. 32 It was found that, under catalytic conditions, reactions with tert -butyl-substituted alkynes resulted in oligomerization to form (noncyclic) trimers through path B ( Figure 8 A, red), while TMS- or phenyl-substituted alkynes preferred linear dimers through path A ( Figure 6 A, black). In 2015, Eisen et al demonstrated that changing from [(Cp*) 2 U(Me) 2 ] ( 5 ) to [(Me 3 Si) 2 U(κ 2 -(N,C)–CH 2 Si(CH 3 ) 2 -N(SiMe 3 )] ( 8 ) allowed for cyclotrimerization to occur ( Figure 4 A, blue), which results in a statistical mixture of 1,2,4- and 1,3,5-arenes ( Figure 8 B) in the cases of phenyl acetylene and tert- butyl acetylene.…”
Section: Oligomerizationmentioning
confidence: 99%